Tlatah Panyucen: Exploration of Website-Based Understanding of Wudhu’ Materials in Students - Widodo, Wahyu; Choiri, Moh Miftachul; Ulum, M Miftahul (JIE (Journal of Islamic Education), 2024)
This research aims to develop a product as a learning media based on the Google site (website) to increase students' understanding of wudhu’ material at SMPN 1 Ponorogo. This research uses a type of development research or research and development (R&D) with the ADDIE style, which is divided into five procedures: analysis, design, development, implementation, and evaluation. Data collection techniques are conducted through interviews, observation, and questionnaires. The research results show that the website media developed by researchers is very effective. This is proven by the significant influence between the results of the pre-test and post-test scores in the experimental class of 0.00 > 0.05, and there is a substantial difference in scores between students' understanding of the wudhu’ material in the experimental class and the control class of 0, 00 > 0.05. Then, website media are practical, as proven by the results of student questionnaire answers: 23.1% delightful, 42.1% happy, 30.8% quite exciting, and 0% not enjoyable. All the data results above show that the website media developed by this researcher is very effective and practical to use as a learning medium at SMPN 1 Ponorogo.